Does a glucose‐based hydrogen and methane breath test detect bacterial overgrowth in the jejunum?. Issue 11 (23rd April 2018) - Sundin, O. H.; Mendoza‐Ladd, A.; Morales, E.; Fagan, B. M.; Zeng, M.; Diaz‐Arévalo, D.; Ordoñez, J.; McCallum, R. W.
Abstract: Background: Direct diagnosis of small intestinal bacterial overgrowth (SIBO) requires the collection and culture of fluid from the jejunal lumen, with a finding of over 10 5 viable bacteria per mL. More often, SIBO is diagnosed indirectly, using a non‐invasive test of the exhaled hydrogen and methane generated by microbial fermentation when ingested glucose reaches the jejunum. Our objective was to determine how well this breath test detects chronic overgrowth of jejunal bacteria that is unrelated to gastrointestinal surgery. Methods: Eighteen patients reporting symptoms consistent with SIBO received a glucose breath test. On a later day, the jejunal lumen was sampled via aspiration during enteroscopy. Jejunal aspirates were cultured on aerobic and anaerobic media. DNA was extracted from the same samples and analyzed by quantitative pan‐bacterial PCR amplification of 16S ribosomal rRNA genes, which provided a culture‐independent bacterial cell count. Key Results: Combined bacterial colony counts ranged from 5.7 x 10 3 to 7.9 x 10 6 CFU/mL. DNA‐based yields ranged from 1.5 x 10 5 to 3.1 x 10 7 bacterial genomes per mL. Microbial viability ranged from 0.3% to near 100%. We found no significant correlation of glucose breath test results with either the number of bacterial colonies or with the DNA‐based bacterial cell counts. Instead, higher signals in the hydrogen‐methane breath test were significantly correlated with a lower viability of jejunal bacteria, at a P ‐value of .014. Conclusions & Inferences: The glucose‐based hydrogen and methane breath test is not sensitive to the overgrowth of jejunal bacteria. However, a positive breath test may indicate altered jejunal function and microbial dysbiosis. Abstract : Breath tests based on the production of hydrogen and methane from the metabolism of ingested glucose are often used to diagnose SIBO. We have found that in a group of patients under evaluation for SIBO, breath test results were not correlated with either PCR‐quantified bacterial DNA or live bacterial counts in jejunal aspirate samples collected during endoscopy. Although the glucose breath test does not appear useful for detecting SIBO, a positive breath test is correlated with low bacterial viability, which may indicate other types of jejunal and dysfunction.